Implementation och design av en databas och ett REST API byggd i .NET Core - Kozma, Cynthia; Nisan, Petra (My University, 2022)
Almost immediately after computers became common in the 1960s, the need for secure data storage developed. Gradually, different types of databases were developed and today the relational database is the most common type. For today’s websites and applications, an advanced database is required to fulfill all the requirements. This report describes how a searchable database has been developed for a prototype mobile-application called Pindle. Pindle is an ongoing project at the company pinDeliver that has a collaboration with the company Elicit Software. The purpose of this project was to investigate how storage of routes can be made efficient and searchable in a database. Additionally, it was determined which data types were most suitable to use in this database that would fulfill the purpose of the application. It was also investigated whether it would be possible to use only two tables in the database and still serve the purpose. Finally, it was investigated whether it would be possible to implement an automatic message sent in a group chat. The project is about creating a suitable database design for the multiple functions that will be available in the application such as save contacts, retrieve the user’s own routes, and optimize them. With the help of a REST API in .NET CORE that creates communication between server and client, various endpoints have been implemented. The code was written in programming languages C# and XAML using the source-code editor Visual Studio Community 2022. The work of the project group was divided into a one-week period based on the agile management methodology. During the project, the couple used Pair Programming as they are quite comfortable with this technology. As a result of this project, a searchable database is created using only two tables that fulfill the purpose of this application-prototype. In addition, an automatic message sent in a group chat was also implemented based on the SignalR framework.
Keywords: Database design; REST API; .NET Core; application; tables; endpoints